1982
DOI: 10.1017/s0022149x00034659
|View full text |Cite
|
Sign up to set email alerts
|

Ascaridoid nematodes of South American mammals, with a definition of a new genus

Abstract: Ascaridoid nematodes occurring in South American mammals are divided into categories based on their possible origin. The affinities are discussed of five species so far known only from the Neotropical Region.Toxocara alienata(Rudolphi, 1819) is reported fromNasua rufa socialis, Procyon cancrivorus, andTayassus torquatus. The specimens fromT. torquatusare described and found most closely to resembleToxocara mackerrasaefrom south-east Asian and Australian rodents.Anisakis insignisfromInia geoffrensisis transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…1 9 . S P R Hartwich (1975) Sprent (1982) Deardorff ( 5 Well anterior to level of cloacal opening. 6 Two united precloacal median papillae (?).…”
Section: Resultsmentioning
confidence: 99%
“…1 9 . S P R Hartwich (1975) Sprent (1982) Deardorff ( 5 Well anterior to level of cloacal opening. 6 Two united precloacal median papillae (?).…”
Section: Resultsmentioning
confidence: 99%
“…A. dussumierii was described from the final hosts Physeter macrocephalus (Physeteridae) and Delphinus delphis (Delphinidae; e.g., Nadler et al 2005), while A. insignis were isolated only from the Amazon dolphin (Inia geoffrensis, Iniidae) and was redescribed by Petter (1972). Sprent (1982) erraneously transferred A. insignis into Peritrachelius Diesing, 1851, giving account to the lip and spicule structure. Different authors previously reported A. alexandri from Stenella frontalis (Delphinidae), but this species was originally described from Sousa chinensis (Delphinidae; Mignucci-Giannoni et al 1998;Perrin 2002).…”
Section: Discussionmentioning
confidence: 99%
“…(both Herpestidae, Carnivora); and G. simiae (Mozgovoy, 1951), established for specimens originally identified by Schuurmans Stekhoven (1937) as Cloeoascaris spinicollis allegedly from the stomach of the monkey Cercopithecus leucampyx kandti Matschiein in the present Democratic Republic of the Congo. However, Sprent (1982) corrected an error in the host record of G. spinicollis to Lutra (= Hydrictis) maculicollis kivuana (Pohle) and considered G. simiae to be a junior synonym of G. spinicollis.…”
Section: D a Bmentioning
confidence: 99%